Characterization of Li₄,Ca₂0₄ and Li₂Mg0₂ using XRD, SEM and UV Vis NiR spectroscopy / Khairi Omar - Omar, Khairi (2012)
Material characterization is a method of determine the physical and chemical properties of a certain material. The scanning electron microscope (SEM) is the most widely used type of electron microscope. It examines microscopic structure by scanning the surface of materials, similar to scanning confocal microscopes but with much higher resolution and much greater depth of field. Ultraviolet-visible spectroscopy or ultraviolet-visible spectrophotometry (UVVis or UV/Vis). Ultraviolet-visible spectroscopy or ultraviolet-visible spectrophotometry (UV-Vis or UVYVis). The absorption in the visible range directly affects the perceived color of the chemicals involved. In this region of the electromagnetic spectrum, molecules undergo electronic transitions. This technique is complementary to fluorescence spectroscopy, in that fluorescence deals with transitions from the excited state to the ground state, while absorption measures transitions from the ground state to the excited state. X-ray diffraction methods are the most effective methods for determining the crystal structure of materials. Diffraction methods can identify chemical compounds from their crystalline structure, not from their compositions of chemical elements. It means that the different compounds (or phases) that have the same composition can be identified